Technostress Creators and Employee’s Well-Being at a Telecommunication Company in Sarawak, Malaysia - Jimmy, Viannie Clairie; Mohamed, Suhaila; Hussein, Norashikin; Anwar, Nur Aizureen; Dahalan, Noor Azura (Information Management and Business Review, 2023)
There are many benefits of technology in the workplace, such as an increase in productivity and knowledge acquisition. However, technological advancement in the workplace may cause technostress. The term technostress refers to the negative psychological relationship between people and adopting new technologies. Technostress occurs when people cannot adequately adapt to or interact with information technologies. The purpose of this study is to determine the relationship between five technostress creators, namely, techno-overload, techno-invasions, techno-complexity, techno-insecurity, and techno-uncertainty towards employee well-being at one Telecommunication Company in Sarawak, Malaysia. The respondents of this cross-sectional quantitative study were 141 individual employees. Data were collected using convenience sampling by utilizing a Google form that was distributed to all populations under the study. The findings of this research indicate a strong relationship between all technostress creators and the well-being of employees. Thus, this research adds to the knowledge of the relationships between technostress creators and employees’ well-being in the workplace. Since the research found that the most prevailing independent variable in this research study is techno-invasion, thus, this research recommended that the company provide guidelines on ICTs use outside of work and take action to limit such work-related interruptions.